From the Editor on Women’s Health: Potential detrimental health effects - Pacheco-Romero, José (2020)
Life expectancy at birth in all countries is above the diagonal parity line – all over the world, a newborn girl can expect to live longer than a newborn boy(1). Because of this, preventive health care should be implemented since birth. In addition, during the reproductive period, gynecologists should advise future mothers to be in good health when getting pregnant and to avoid unintended or forced pregnancies and potential environmental threats to the fetus. A group of researchers has found that black carbon particles accumulate on the fetal side of the placenta; this suggests that ambient particulates could be transported towards the fetus(2). Pregnant women who are exposed to higher air pollution levels during their second pregnancy may be at greater risk for preterm birth, when compared with their first pregnancy(3).